Hubungan Merokok Dan Riwayat Keturunan Dengan Kejadian Hipertensi - Nanang Dismiantoni; Anggunan Anggunan; Nia Triswanti; Rina Kriswiastiny (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Smoking is an overt behavior in which smokers inhale tobacco rolls. In this case, it means that smoking is inhaling a roll of tobacco that wrapped in a paper. History of descent is if both parents have a history of the disease, then their descent will be at risk for getting the disease because of the genetics influence. Hypertension is a condition when the systolic blood pressure ≥ 140 mmHg and diastolic ≥ 90 mmHg on two blood pressure measurement examinations within 5 minutes and in a relaxed state. Methodology: The type of research that is used is patients that are suspected of having hypertension in the working area of Community Health Center (PUSKESMAS observational analytic method with cross-sectional approach by using a questionnaire. The population of this study was all) Simbarwaringin in Trimurjo district of Central Lampung in 2019. As well as sampling using purposive sampling method, with a total of 88 samples. The data were analyzed by Chi-Square test. Result: In this study, out of 42 respondents who have a smoking habit, most experienced hypertension as many as 36 people (85.7%). Similarly of the 59 respondents who have hereditary factors, most experienced hypertension as many as 48 people (81.4%). By using the Chi-Square test, shows that a p-value = 0.016 which is less than the value of significance of 5%. It shows a significant relationship between smoking habit with the incidence of hypertension and also a relationship of hereditary with the incidence of hypertension by using Chi-Square showed a p-value = 0.023 which is less than the value of significance of 5% (0.05). Conclusion: There is a relationship between smoking and the history of descent with hypertension events in the working area of Community Health Center (PUSKESMAS) Simbarwaringin in Trimurjo district of Central Lampung in 2019.